2013
DOI: 10.1002/cncr.28262
|View full text |Cite
|
Sign up to set email alerts
|

Are survivors who report cancer‐related financial problems more likely to forgo or delay medical care?

Abstract: BACKGROUND Financial problems caused by cancer and its treatment can substantially affect survivors and their families and create barriers to seeking health care. METHODS The authors identified cancer survivors diagnosed as adults (n = 1556) from the nationally representative 2010 National Health Interview Survey. Using multivariable logistic regression analyses, the authors report sociodemographic, clinical, and treatment-related factors associated with perceived cancer-related financial problems and the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
322
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 339 publications
(351 citation statements)
references
References 37 publications
(76 reference statements)
21
322
5
Order By: Relevance
“…Compared with non-CCEP participants, those enrolled in the CCEP were younger and had lower incomes. Studies have shown that, in general, younger patients and those with lower incomes experience considerable cancer-related financial problems [24,[48][49][50][51]. We also found that a higher proportion of CCEP participants were enrolled in phase I clinical trials and had metastatic disease.…”
Section: Discussionmentioning
confidence: 53%
“…Compared with non-CCEP participants, those enrolled in the CCEP were younger and had lower incomes. Studies have shown that, in general, younger patients and those with lower incomes experience considerable cancer-related financial problems [24,[48][49][50][51]. We also found that a higher proportion of CCEP participants were enrolled in phase I clinical trials and had metastatic disease.…”
Section: Discussionmentioning
confidence: 53%
“…11,12 Second, personal finances are recognized as an important factor in patients' ability to receive optimal therapy for cancer. 34 Anywhere from 9% to 20% of cancer patients report missing essential medical care because of personal cost, 12,35,36 and the likelihood of economically-motivated nonadherence is even greater among cancer patients who are younger, 35 have the lowest incomes, 12 or are uninsured. 36 Furthermore, disease-related job loss and disability substantially increase nonadherence with recommended cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Concern about medical cost precipitated harmful health behaviors in one-third of the study population; those who were retired were more likely to exhibit treatment noncompliance due to financial reasons. In their study of 1556 cancer survivors, Kent et al 29 concluded that those who reported cancer-related financial problems were more likely to report delaying medical care (18.1 vs 7.4%; P o 0.0001) or forgoing medical care (13.5 vs 5.1%; P o0.0001) and prescription medications (13.8 vs 7.7%; P = 0.001) than those without financial problems. 29 Arora et al 30 found that patients with low income were over three times as likely to report frailty after transplant.…”
Section: Functional Considerationsmentioning
confidence: 99%
“…In their study of 1556 cancer survivors, Kent et al 29 concluded that those who reported cancer-related financial problems were more likely to report delaying medical care (18.1 vs 7.4%; P o 0.0001) or forgoing medical care (13.5 vs 5.1%; P o0.0001) and prescription medications (13.8 vs 7.7%; P = 0.001) than those without financial problems. 29 Arora et al 30 found that patients with low income were over three times as likely to report frailty after transplant. 23 Therefore, financial stress negatively impacts patients' long-term health and ongoing treatment decisions.…”
Section: Functional Considerationsmentioning
confidence: 99%